An Outbreak of Human Coronavirus OC43 Infection and Serological Cross-Reactivity with SARS Coronavirus - David M Patrick; Martin Petric; Danuta M Skowronski; Roland Guasparini; Timothy F Booth; Mel Krajden; Patrick McGeer; Nathalie Bastien; Larry Gustafson; Janet Dubord; Diane MacDonald; Samara T David; et al. (Canadian Journal of Infectious Diseases and Medical Microbiology)
BACKGROUND: In summer 2003, a respiratory outbreak was investigated in British Columbia, during which nucleic acid tests and serology unexpectedly indicated reactivity for severe acute respiratory syndrome coronavirus (SARS-CoV).